THE SOUND PARADIGM OF VASYL STEFANYK’S NOVELLA «A STONE CROSS» - Horbolis, Larysa (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2022)
The aim. The article suggests a new view on the organization and structure of Vasyl Stefanyk’s novella “A Stone Cross” that determines the elucidation of an intermedial issue in the analysis of the writer’s famous work: the unity of a word and sound palette in the fictional text of the novella author’s prose. Therefore, the aim of the article is to study through the prism of one novella a general tendency of Vasyl Stefanyk’s creative work: the synthesis of literature and art, the study of methodological approaches to interpreting the phenomena of intermediacy in the novellas of the classic of our national literature. The research methods. For the analysis the synthesis of principles and methods of scientific researchis implemented, first of all, of intertextual, comparative-typological, intermedial, poetological and biographical ones. The research results. The interpretation of Vasyl Stefanyk’s novella “A Stone Cross” through the prism of verbal and music-sound aspects promotes understanding of the writer’s rich in senses well-known work. That is why the selected poetic analysis of each part of “A Stone Cross” is the most acceptable for researching the textual longevity of sounds and music in the novella’s general structure. In the research process of the sound paradigm of Vasyl Stefanyk’s work, its groundbreaking essence, the peculiarity of its style, modern poetics are proved that undoubtedly affected the precision and powerful energy of its word form. The scientific novelty. In the research there is achieved a new reading of the text of Vasyl Stefanyk’s novella “A Stone Cross”, for the first time there is performed the analysis of its sound contour by means of which the subtexts and hidden senses of the work are decoded. Such a cutting-edge approach proposes a fresh view on the Ukrainian author’s modernistic searches: the sound, music, song, dance identify the main hero Ivan Didukh, generally psychologise the text of the work. The practical significance. The obtained research results may be used in further research of Vasyl Stefanyk’s creative work from positions of contemporary literary studies, particularly the proposed interpretational approach is one of the segments of a poly-aspectual interpretation of the deep in its contents work that has already become classical both in the sphere education and in scientific studies of today’s researchers of Vasyl Stefanyk’s creative work.